Breaking with mainstream politics while engaging with polarized: Determinants of young Europeans’ support for democracy - Belchior, A. M. da C.; Teixeira, C. P. (Journal of Youth Studies, 2024)
It is quite consensual that the younger citizens exhibit higher – although objectively modest – scepticism about democracy and openness to undemocratic forms of government. Despite the ongoing debate about whether a process of deconsolidation is underway in liberal democracies, as well as about the role of young citizens in it, research has so far given little attention to finding out why younger people are more likely to turn away from democracy. Seeking to contribute to filling this gap, we focus on exploring the determinants of young Europeans’ support for democracy and non-democratic forms of government, and the extent to which these determinants differ from that of older citizens. Our claim is that young people's detachment from mainstream politics and political polarization are crucial factors underlying that tendency. The findings generally support our expectations.